2011
DOI: 10.1038/tp.2011.57
|View full text |Cite
|
Sign up to set email alerts
|

Positive autoregulation of GDNF levels in the ventral tegmental area mediates long-lasting inhibition of excessive alcohol consumption

Abstract: Glial cell line-derived neurotrophic factor (GDNF) is an essential growth factor for the survival and maintenance of the midbrain dopaminergic (DA-ergic) neurons. Activation of the GDNF pathway in the ventral tegmental area (VTA), where the GDNF receptors are expressed, produces a long-lasting suppression of excessive alcohol consumption in rats. Previous studies conducted in the DA-ergic-like cells, SHSY5Y, revealed that GDNF positively regulates its own expression, leading to a long-lasting activation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 47 publications
1
65
0
Order By: Relevance
“…The placement of the ethanol bottle is alternated each drinking session to control for side preferences. Drinking sessions can begin during the light cycle (Barak, Ahmadiantehrani, Kharazia, & Ron, 2011; Barak, Carnicella, Yowell, & Ron, 2011; Carnicella, Amamoto, et al, 2009; Carnicella et al, 2008) or the dark cycle (Li, Bian, Dave, & Ye, 2011; Simms et al, 2008). Fluid intake is recorded at various time points, usually 30–60 min and 24 h after the beginning of the session.…”
Section: Intermittent Access To 20% Alcohol In 2-bottle Choicementioning
confidence: 99%
“…The placement of the ethanol bottle is alternated each drinking session to control for side preferences. Drinking sessions can begin during the light cycle (Barak, Ahmadiantehrani, Kharazia, & Ron, 2011; Barak, Carnicella, Yowell, & Ron, 2011; Carnicella, Amamoto, et al, 2009; Carnicella et al, 2008) or the dark cycle (Li, Bian, Dave, & Ye, 2011; Simms et al, 2008). Fluid intake is recorded at various time points, usually 30–60 min and 24 h after the beginning of the session.…”
Section: Intermittent Access To 20% Alcohol In 2-bottle Choicementioning
confidence: 99%
“…It should be noted however, that although the responsiveness of the GDNF gene to alcohol is altered after chronic excessive drinking, the pathway itself appears to be unperturbed. The likelihood of this possibility is supported by the fact that infusion of exogenous GDNF protein into the VTA of chronically drinking rats causes a reliable and rapid decrease in both operant selfadministration (Barak, Carnicella, et al, 2011;Carnicella et al, 2008) and voluntary consumption of alcohol (Barak, Ahmadiantehrani, et al, 2011;Carnicella, Amamonto, et al, 2009). Interestingly, studies in humans have reported significantly reduced BDNF (Joe et al, 2007) and GDNF (Heberlein et al, 2010) levels in the blood serum of alcohol-dependent subjects, strongly corroborating the idea that the dysregulation of these protective signaling proteins is an evolutionarily conserved neuroadaptation to long-term, repeated cycles of excessive drinking and withdrawal.…”
Section: Dysregulation Of Protective Genesmentioning
confidence: 96%
“…In a series of recent studies, we found that the GDNF-mediated signaling pathway in the VTA is a potent negative regulator of excessive alcohol consumption and reinforcement. Specifically, infusion of the growth factor into the rat VTA, a region in which the GDNF receptors Ret and GFR1 are expressed, induced a rapid and robust activation of ERK1/2 and a corresponding decrease of excessive alcohol in a 2BC model of voluntary excessive drinking and operant self-administration (Barak, Ahmadiantehrani, Kharazia, & Ron, 2011;Carnicella, Kharazia, Jeanblanc, Janak, & Ron, 2008;. Furthermore, GDNF also blocked relapse to alcohol seeking (Carnicella et al, 2008) as well as acquisition and expression of conditioned place preference (CPP) for alcohol .…”
Section: Protective Signaling Pathwaysmentioning
confidence: 97%
“…Glial cell line-derived neurotrophic factor (GDNF) is a protein that is essential for the maintenance and survival of dopamine (DA) neurons (Boger et al, 2006) and can inhibit microglial activation (Rocha, Cristovão, Campos, Fonseca, & Baltazar, 2012). Additionally, preclinical evidence suggests that infusion of GDNF into the ventral tegmental area (VTA) blocks the acquisition and expression of alcohol-induced conditioned place preference (Barak, Ahmadiantehrani, Kharazia, & Ron, 2011;Barak, Carnicella, Yowell, & Ron, 2011), rapidly reduces alcohol intake (Carnicella, Ahmadiantehrani, Janak, & Ron, 2009, Carnicella, Amamoto, & Ron, 2009Carnicella, Kharazia, Jeanblanc, Janak, & Ron, 2008), and blocks alcohol reinstatement following extinction (Carnicella et al, 2008). Furthermore, endogenous levels of GDNF have been found to negatively regulate the rewarding effect of alcohol after a period of abstinence (Carnicella, Ahmadiantehrani, et al, 2009;Carnicella, Amamoto, et al, 2009).…”
Section: Neuroinflammation and Alcohol Dependencementioning
confidence: 99%
“…In one human study, GDNF serum levels measured peripherally were found to be significantly reduced in alcohol-dependent patients versus healthy controls and to be negatively associated with measures of tolerance and withdrawal (Heberlein et al, 2010). It has been hypothesized that GDNF functions to reduce these alcohol-related behaviors in animal models by reversing an alcohol-induced allostatic DA deficiency in the mesolimbic system caused by prolonged excessive alcohol consumption and repeated withdrawal (Barak, Ahmadiantehrani, et al, 2011;Barak, Carnicella, et al, 2011). Furthermore, there is evidence that pharmacological inhibition of phosphodiesterase-4 (PDE4), an enzyme that hydrolyses cyclic adenosine monophosphate (cAMP), decreases alcohol intake in mice (Hu et al, 2011) and rat (Wen et al, 2012) models of alcoholism, as well as reduces neuroinflammation and neuronal death in rats .…”
Section: Neuroinflammation and Alcohol Dependencementioning
confidence: 99%